Masa Jabatan Kepala Desa Bangunharjo Kecamatan Sewon Kabupaten Bantul: Ditinjau dari Undang-Undang Nomor 6 Tahun 2014 tentang Desa - Iis Qomariyah (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2014)
The research concludes that the legal basis used Bangunharjo village chief areLaw No. 22 of 1999 on Regional Government. In Article 96 describes the "villagechief tenure of ten years or a maximum of two terms as of the date specified." Thoughthe law declared invalid because it has been replaced Law No. 32 of 2004 inconjunction with Law No. 12 of 2008 on Regional Government. The term of office ofsix years and the village chief can only be re-elected for a subsequent term of office.However, the researchers did a special case of the Village Head Bangunharjo serve timeover regulated by the Act. Term of office of the Village Head Bangunharjo not inaccordance with Law No. 6 2014 because the Act states that the village chief in officefor 6 years. Then be served at most three consecutive terms consecutively or notconsecutively. Basically the most recent regulations crippling/cancel the old rules, so therules have been replaced with the new rules, the old rules are automatically void.